Impact of atomizer design on slurry fuel atomization behavior - Kuznetsov G. V. Geny Vladimirovich; Podgornaya E. R. Elizaveta Romanovna; Strizhak P. A. Pavel Alexandrovich; Volkov R. S. Roman Sergeevich (2024, 2024)
Title screen.